Strategi Sales Admin dalam Mengelola Event Pesparawi Jambi di Gallery Prawirotaman Hotel Yogyakarta - Jelita Anjani; Amin Kiswantoro; Damiasih Damiasih; Dwiyono Rudi Susanto; Rizky Maulana (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The Jambi Pesparawi event is an annual event organized by members of the Church Choir and is a target market segment for hotels that need to be handled properly, for that the hotel must have a strategy so that the event can be held at Gallery Prawirotaman Hotel Yogyakarta. This study aims to find out how the strategy carried out by the sales admin in managing the Jambi Pesparawi Event. This study used the Case Study research method at the Jambi Pesparawi Event at the Gallery Prawirotaman Hotel Yogyakarta. The results showed that the strategy carried out by the Sales Admin of the Prawirotaman Hotel Yogyakarta Gallery was divided into three stages, namely the event planning stage, the event implementation stage, and the post-event stage.